The effect of bioactive polyphenols from anacardium occidentale linn. Leaves on α-amylase and dipeptidyl peptidase iv activities - Abdullah Thaidi, Nur Imanina; Mat Jusoh, Hanapi; Ghazali, Ahmad Badruddin; Haron, Normah (Gagjah Mada University, 2019)
Anacardium occidentale Linn. (A. occidentale L.) leaves possess an excellent source of bioactive compounds, which are associated with numerous health benefits including antidiabetic potency for the management of type 2 diabetes mellitus (T2DM). The management strategies for T2DM include to maintain the postprandial blood glucose level through the inhibition of α-amylase and to prevent the hydrolysis of glucagon like peptide-1 (GLP-1) through the inhibition of dipeptidyl peptidase IV (DPPIV). In this study, free, soluble ester and insoluble bound phenolic fractions from young and matured leaves of A. occidentale L. were extracted and analyzed using high performance liquid chromatography (HPLC). Subsequently, all fractions were investigated for their inhibitory effect on α-amylase and DPPIV enzymes activities. Both free (72.45 ± 3.6%) and soluble ester (83.40 ± 4.7%) phenolic fractions in the matured leaves extracts had significantly demonstrated greater α-amylase inhibitors than the young leaves. Likewise, soluble ester (4.09 ± 0.34 µg/ml) and insoluble bound (4.87 ± 0.32 µg/ml) phenolic fractions in the matured leaves extracts were significantly more effective in inhibiting DPPIV than the young leaves. As for fractions comparison, insoluble bound derived from the young leaves extract was a more potent α-amylase inhibitor than free and soluble ester phenolic fractions (p<0.0001). In addition, soluble ester and insoluble bound phenolic fractions showed a stronger inhibitor of DPPIV than free phenolic (p<0.001), irrespective of maturity of the leaves. In conclusion, this study showed that A. occidentale L. extracts possessed antidiabetic properties which may potentially be used as an alternative treatment for T2DM management.